2013
DOI: 10.3727/096368913x672136
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study Shows Safety and Efficacy of Autologous Bone Marrow Mononuclear Cell Therapy to Improve Quality of Life in Muscular Dystrophy Patients

Abstract: Muscular dystrophy is a genetic disorder with no definite cure. A study was carried out on 150 patients diagnosed with muscular dystrophy. These included Duchenne muscular dystrophy, limb-girdle muscular dystrophy, and Becker muscular dystrophy variants. They were administered autologous bone marrow-derived mononuclear cells intrathecally and intramuscularly at the motor points of the antigravity weak muscles followed by vigorous rehabilitation therapy. No significant adverse events were noted. Assessment afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Their safety and efficacy has already been established in other neurological disorders. [19][20][21][22][23][24][25][26] These cells are a mixture of various hematopoietic and non hematopoietic cells which are more potent in combination as compared to their individual fractions. On transplantation, they migrate to the damaged areas and initiate repair.…”
Section: Discussionmentioning
confidence: 99%
“…Their safety and efficacy has already been established in other neurological disorders. [19][20][21][22][23][24][25][26] These cells are a mixture of various hematopoietic and non hematopoietic cells which are more potent in combination as compared to their individual fractions. On transplantation, they migrate to the damaged areas and initiate repair.…”
Section: Discussionmentioning
confidence: 99%
“…First, autologous bone marrow mononuclear cells, which have myogenic potential, were infused, and provided evidence for the putative benefits of cellular therapy in altering the disease progression [55,56]. Second, boosting of NO-cGMP signaling is a target for BMD treatment, because nNOS is deregulated in BMD [57].…”
Section: Clinical Trials In Bmd Patientsmentioning
confidence: 99%
“…Being autologous, these cells are a safe treatment modality; and, because these are adult stem cells, they are not prone to developing tumorigenic attributes. Multiple clinical trials, in a variety of neurological ailments, have demonstrated the safety and efficacy of adult autologous BMMNCs as a therapy [12][13][14]41 . None of the studies have shown any major or irreversible adverse events post transplantation.…”
Section: Table 1: Changes In Outcome Measures Over a Period Of 18 Monmentioning
confidence: 99%
“…Effective therapies for halting disease progression and improving quality of life are the need of the hour. Various studies worldwide advocate the efficacy and safety of autologous bone marrow-derived mononuclear cells (autologous BMMNCs) as a therapeutic intervention for neurological disorders [12][13][14] , including for ALS [15][16][17] . Lithium not only increases the survival and potency of these transplanted cells 18 , but is also safe when administered to ALS patients 19,20 .…”
Section: Introductionmentioning
confidence: 99%